Quest for the spark : Book One - Sniegoski, Tom; Smith, Jeff (New York : Scholastic, 2011)
Twelve-year-old Tom Elm, his raccoon friend Roderick, Percival, Abbey, and Barclay Bone, warrior-priest Randolf, and forest-woman Lorimar join in a quest to find the pieces of the Spark that can save Dreaming--and the Waking World--from a Darkness created by the Nacht.
Keywords: fantasy -- Fiction